2005
DOI: 10.1111/j.1365-2516.2005.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Can activated recombinant factor VII be used to postpone the exposure of infants to factor VIII until after 2 years of age?

Abstract: Two retrospective studies have suggested that exposure to factor VIII (FVIII) in early infancy is associated with an increased risk of FVIII inhibitor development. We prospectively studied 11 infants who needed replacement therapy for bleeding episodes before the age of 2 years. They received activated recombinant factor VII (rFVIIa) concentrate on demand, with the intention of postponing their first exposure to FVIII after 2 years of age. Thirty-three bleeding episodes were treated with 154 doses of rFVIIa wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…in a small pilot study in which the aim was to use rFVIIa in place of FVIII until the age of 2 years. Of the 11 infants in this study, six still required FVIII to control bleeding and four subsequently developed inhibitors, which suggests that this is unlikely to be a feasible approach [11].…”
Section: Discussionmentioning
confidence: 99%
“…in a small pilot study in which the aim was to use rFVIIa in place of FVIII until the age of 2 years. Of the 11 infants in this study, six still required FVIII to control bleeding and four subsequently developed inhibitors, which suggests that this is unlikely to be a feasible approach [11].…”
Section: Discussionmentioning
confidence: 99%
“…Rivard and colleagues completed a prospective trial in 11 pediatric patients with severe hemophilia using recombinant factor VIIa to try and postpone exposure to FVIII until after 2 years of age [Rivard et al 2005]. Owing to inadequate hemostasis with recombinant factor VIIa, especially in mouth bleeding, only 3 out of 11 children could postpone FVIII exposure until after 2 years of age [Rivard et al 2005], making this therapeutic option limited. Challenges remain as to the most effective manner in which to minimize a patient's risk of inhibitor formation and further studies are required.…”
Section: Stratification Of Inhibitor Riskmentioning
confidence: 99%
“…Somewhat paradoxically, it was reported that inhibitor formation was more frequent in patients that initiated IV injections of human FVIII before 6 months of age than for those that started therapy after 6 months [Lorenzo et al, 2001;van der Bom et al, 2003], which would appear to argue against using early administration of protein therapy to prevent inhibitors. However, other studies suggest that the specific hFVIII mutation and/or initiation with episodic therapy in response to bleeds rather than frequent prophylaxis may be critical [Rivard et al, 2005;Chalmers et al, 2007;Santagostino et al, 2005;Kulkarni et al, 2006]. A trial in which protein therapy is initiated with high and frequent administration of human FVIII would be difficult due to problems with IV access in newborn patients.…”
Section: Efficacy Of Neonatal Tolerance To Human Fviii In Humansmentioning
confidence: 94%